In situ small angle X-ray scattering investigation of ultrasound induced nucleation in a metallic alloy melt. (September 2015) - Huang, Haijun; Shu, Da; Zeng, Jianrong; Bian, Fenggang; Fu, Yanan; Wang, Jun; Sun, Baode
Abstract : An in situ synchrotron small angle X-ray scattering (SAXS) method was employed to probe the change of scattering structures in an Al–Cu alloy melt after ultrasonic melt treatment. The size distribution and fractal geometry of the scatterers were evaluated by quantitative SAXS analysis. Results show that cavitation induced nuclei on the clusters or impurities, and the remnants, showing bigger sizes and lower surface fractal dimensions in a melt of lower superheating, could preserve grain refining potential for at least 20 min.